The Effect of Marketing Mix on Sales Volume of Suzuki Ertiga Cars at PT. Megahputra Sejahtera Pettarani Makassar Branch - Muhammad Ichwan Musa; Putri Abadi Handayani (Economics and Business Journal (ECBIS), 2023)
This study aims to determine the effect of marketing mix on sales volume at PT. Megahputra Prosperous Pettarani Makassar Branch. The population in this study are consumers at PT. Megahputra Sejahtera Pettarani Makassar Branch who purchased Suzuki Ertiga car products in 2018-2022. Data collection was carried out using documentation and questionnaire methods. The data analysis technique used is multiple linear regression analysis. Multiple linear regression equations produce equations Y ̂= 0.308+ 0.248X_1+ 0.009X_2+ 0.027X_( 3)+ 0.094X_4 + ( -0.151 ) X_5+ 0.403X_6 + 0.137X_7. This the results of this study found that simultaneously the Marketing Mix variable (X1, X2, X3, X4, X6, and X7) has a positive effect on Sales Volume while X5 has a negative effect on Sales Volume. The results of the determination correlation analysis (R Square) were 0.343 which indicated that 34.3% of the independent variables namely X1, X2, X3, X4, X5, X6, and X7 had an effect or were able to explain the characteristics of the dependent variable (Y). While the remaining 65.7% is influenced or explained by other variables not included in this research model. The results of the F test explain that the seven Marketing Mix variables have a significant effect on the Sales Volume variable with a calculated F value (6.157) > F table (2.16) with a significance level of 0.000 <0.05 and the t test results explain that the Product variable (X1) with value 0.017 <0.05 and Process (X6) with a value of 0.001 <0.05 has a significant effect on Sales Volume variable